Digitalisasi UMKM sebagai Penyuluhan Pembangunan Ekonomi Berkelanjutan di Desa Wanasari - Mujab Fahmi Suhud; Tiwi Sri Pujiawati; Indra Priana; Dede Sulaeman (Journal of Innovative and Creativity, 2025)
The development of digital technology has had a major impact on the economic sector, especially on Micro, Small, and Medium Enterprises (MSMEs) which are the backbone of the local economy in Indonesia. The digitalization of MSMEs allows for increased operational efficiency, market expansion, and higher competitiveness. The Covid-19 pandemic has accelerated the transformation of digital MSMEs as a strategy for economic adaptation and recovery. However, obstacles such as low digital literacy and limited human resources are still the main challenges. The community service program in the form of a seminar "Digital Smart MSMEs, Economically Developed Villages Grow" in Wanasari Village using the Participatory Action Research (PAR) method aims to improve the understanding and digital capabilities of the local community. The results show a significant increase in the use of social media, e-commerce, business management tools, and digital marketing strategies by MSME actors. Digitization of MSMEs plays an important role in improving the welfare of the village economy by creating new jobs, expanding access to national and international markets, and strengthening food security through collaboration between sectors. Thus, digitalization is not just a technological advancement, but an instrument of inclusive and sustainable economic development strategies in this modern era.